2010
DOI: 10.1111/j.1440-1843.2010.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the highest frequency of breath sounds without wheezing during methacholine inhalation challenge in children

Abstract: Methacholine-induced bronchoconstriction significantly increased HFI, and the increase in HFI was correlated with bronchial reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…These results are contradictory to the theory proposed by Hardin and Patterson (1979), but in agreement with observations of lung sound over a range of flow rates in the inspiratory maneuver (Gavriely and Cugell, 1996;Harper, et al, 2003). In some further studies, it was found that the characteristics of the inspiratory sound (mean, median, or the highest frequency) were changed when the patient performed a methacholine challenge test (Habukawa et al, 2010). The change in the PSD distribution profile of the lung sound could therefore be a clear indicator of the severity of the bronchoconstriction in the lung airway.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…These results are contradictory to the theory proposed by Hardin and Patterson (1979), but in agreement with observations of lung sound over a range of flow rates in the inspiratory maneuver (Gavriely and Cugell, 1996;Harper, et al, 2003). In some further studies, it was found that the characteristics of the inspiratory sound (mean, median, or the highest frequency) were changed when the patient performed a methacholine challenge test (Habukawa et al, 2010). The change in the PSD distribution profile of the lung sound could therefore be a clear indicator of the severity of the bronchoconstriction in the lung airway.…”
Section: Discussioncontrasting
confidence: 56%
“…The measurements taken from a location downstream from the constriction did not agree with the OASPL data. In a real human lung, bronchoconstriction is known to change the properties of the lung sound (Habukawa et al, 2010;Schreur et al, 1995;Spence et al, 1992), although specific parameters that can objectively predict the bronchoconstriction level are still under investigation. Bronchoconstriction can appear at several locations in peripheral airways simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study emphasized the importance of inspiratory frequency, which had a stronger relationship with FEV 1 %pre-dicted and %FEV 75 , and FEV 1 -FVC than expiratory frequency in children with asymptomatic asthma, and the other study emphasized the usefulness of analyzing the changes in expiratory frequency, which were significantly associated with the changes in spirometric parameters and bronchial hyperresponsiveness during methacholine inhalation provocation. 10 The inspiratory and expiratory phases may have their own characteristics that have not yet been confirmed. As a possible solution, we calculated the E-I LF as an index of the ratio of the sound power at inhalation and exhalation, which may be more informative.…”
Section: Discussionmentioning
confidence: 98%
“…Each of the highest frequencies at inspiration or expiration is inversely correlated with airway obstruction. 9,10 Notably, airway inflammation is an important factor in the diagnosis and/or evaluation of the effects of treatment of patients with asthma. The degree of airway inflammation is now assessed by performing a bronchial biopsy and a bronchial lavage with a fiberoptic bronchoscope, which are invasive; by inducing sputum by using a hypertonic saline solution inhalation, which is cumbersome or unstable to be obtained; and by analyzing exhaled breath condensate or measuring exhaled nitric oxide (FeNO), which are expensive.…”
mentioning
confidence: 99%